Linnaeus’ Hammarby, Uppsala University - Jesper Kårehed (Uppsala University, 2026)
Linnaeus bought his summer estate Hammarby in 1758 and made it in a sense to a private research facility where we still today can study about forty plant species surviving from Linnaeus's days.
Keywords: Occurrence; OCCURRENCE; Biological Sciences; Biologi